Defining hierarchies of stemness in the intestine: evidence from biomarkers and regulatory pathways - Gracz, A. D. (American Physiological Society, 2014)
For decades, the rapid proliferation and well-defined cellular lineages of the small intestinal epithelium have driven an interest in the biology of the intestinal stem cells (ISCs) and progenitors that produce the functional cells of the epithelium. Recent and significant advances in ISC biomarker discovery have established the small intestinal epithelium as a powerful model system for studying general paradigms in somatic stem cell biology and facilitated elegant genetic and functional studies of stemness in the intestine. However, this newfound wealth of ISC biomarkers raises important questions of marker specificity. Furthermore, the ISC field must now begin to reconcile biomarker status with functional stemness, a challenge that is made more complex by emerging evidence that cellular hierarchies in the intestinal epithelium are more plastic than previously imagined, with some progenitor populations capable of dedifferentiating and functioning as ISCs following damage. In this review, we discuss the state of the ISC field in terms of biomarkers, tissue dynamics, and cellular hierarchies, and how these processes might be informed by earlier studies into signaling networks in the small intestine.